Neočekávaný nález cizího tělesa v oblasti kolenního kloubu desetiletého chlapce - Hanus, Martin; Hladký, Vít (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2021)
Differential diagnosis of tumor processes in orthopedics is a relatively broad and inherently very serious issue, especially if the patients are pediatric patients. A number of examination procedures is used in diagnostics, together with a wide range of complementary laboratory and imaging methods. However, the clinical examination, including the collected anamnestic data, remains to be the cornerstone. In pediatric patients, of major importance is the cooperation with parents, but not always necessary information is provided to make the final diagnosis. In younger children, it is very often impossible to obtain relevant anamnestic data due to a number of factors that are typical for pediatric patients, namely fear, noncooperation, misunderstanding of questions, mainly as a result of mental immaturity. Therefore, diagnosis in these cases is based primarily on clinical and complementary findings. This work presents a complex issue of this diagnosis, with a surprising and unexpected finding of a foreign body in the knee joint of a pediatric patient, which completely changed the subsequent treatment strategy. It concerned a 10-year-old boy referred to our clinic from another workplace for suspected tumor process in the knee joint. The whole process of examination and final diagnosis depends on a number of detailed information that we have tried to obtain throughout the process. Key words: tumor, knee, foreign body, diagnostics, imaging methods.
Keywords: cizí tělesa; Diagnosis, Differential; lidé; Knee Joint; Foreign Bodies; dítě; Child; Humans; diferenciální diagnóza; Male; mužské pohlaví; kolenní kloub